PENGARUH PERLAKUAN BODY SHAMING TERHADAP KEPERCAYAAN DIRI MAHASISWA BIMBINGAN DAN KONSELING - Siqma Freshtin; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Along with the development of appearance style and physical character during adolescence, verbal abuse often happen in the form of body shaming. Body shaming are very influential on the self-confidence of adolescents. It’s because in adolescence, self-confidence is very important, especially to build interactions with friends and their environment. Body shaming that a teenager receives will indirectly undermine his self-confidence. This study aims to determine the significance effect of the body shaming treatment towards self-confidence on class of 2020 of Guidance and Counseling students at Satya Wacana Christian University. This type of research is causal comparative. The research sample was taken using a total sampling technique according to the total population of 48 students. The data collection technique uses a questionnaire instrument with 4 alternative answers. The research data were analyzed using a simple linear regression technique using SPSS 23. The results showed that the acquisition of tcount> ttable (-10,220 > 2,013) and a significance value of 0.000 < 0.05. So it can be concluded that in this study there was a negative significant effect of the body shaming treatment towards the self-confidence on class of 2020 Guidance and Counseling students at Satya Wacana Christian University.